Effect of the Magnetic Field on the Values of Temperature and Density Electron in Discharge Electric Gases N2 and CO2 - Hatem K. Mohaisen; Abdlhussain A.Khadyair; Ahmed H. Wanas (Al-Qadisiyah Journal of Pure Science, 2018)
In this research the influence of magnetic field on the degree of electron temperature and concentration of electrons of plasma dual dioxide and plasma nitrogen different poles (iron and aluminum) was studies using the probe Langmore When low for pressure ranges from    (0.153-0.76 torr) the distance between the poles (25cm). We have noted  a difference in the degree of electron temperature for different gas was found that the degree of electron temperature nitrogen is higher than the temperature of the electron to a binary dioxide and there is a difference in the concentration of electrons. We also found that the electron temperature and the concentration of electrons varies depending on the work function metal, and when we put a magnetic field on the plasma will drop the temperature of the electron and increases the concentration  of electrons